Mendorong Penegakan Hak Dan Kewajiban Negara Dalam Melestarikan Hewan Laut - Farah Fidela; Tiara Jelita Andalusianti Roozan; Hasrinda Rizqi Pramassari; Rajwa Al Imtiyaz; Vanesa Alexandro Caniago; Rani Pajrin (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2024)
This study aims to analyze the rights and obligations of states in an effort to conserve marine animals and encourage the enforcement of related international legal principles. Marine animals are natural resources that are vulnerable to overexploitation and environmental damage. States have the right to utilize marine resources, but are also obliged to protect marine biodiversity in accordance with the principles of international law. This research uses a normative approach by examining international legal instruments such as the United Nations Convention on the Law of the Sea (UNCLOS) and the Convention on Biological Diversity (CBD), as well as related national laws and regulations. The results showed that the country must uphold the principle of sustainable use of marine resources and protect marine ecosystems from damage. This enforcement can be done through international cooperation, strengthening regulations, and empowering local communities. This research provides recommendations to strengthen law enforcement in conserving marine animals and ensuring a balance between state rights and obligations.